2022
DOI: 10.3389/fimmu.2022.909275
|View full text |Cite
|
Sign up to set email alerts
|

Innate Lymphoid Cells - Neglected Players in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a highly debilitating autoimmune disease affecting millions of individuals worldwide. Although classically viewed as T-cell mediated disease, the role of innate lymphoid cells (ILC) such as natural killer (NK) cells and ILC 1-3s has become a focal point as several findings implicate them in the disease pathology. The role of ILCs in MS is still not completely understood as controversial findings have been reported assigning them either a protective or disease-accelerating role. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…IL-2 production was impaired in PwMS independently of the booster dose, whereas HCWs showed an IL-2 specific T-cell response. IL-2 is involved in the cell activation associated with a worsening of the MS disease status33; therefore, the IL-2 production impairment may indirectly explain the lack of MS worsening symptoms after SARS-CoV-2 vaccination. Interestingly, an impaired IL-2 production was also found in COVID-19 vaccinated patients with other autoimmune diseases, including rheumatoid arthritis 34…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 production was impaired in PwMS independently of the booster dose, whereas HCWs showed an IL-2 specific T-cell response. IL-2 is involved in the cell activation associated with a worsening of the MS disease status33; therefore, the IL-2 production impairment may indirectly explain the lack of MS worsening symptoms after SARS-CoV-2 vaccination. Interestingly, an impaired IL-2 production was also found in COVID-19 vaccinated patients with other autoimmune diseases, including rheumatoid arthritis 34…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a well-known autoimmune disease that affects the central nervous system. Numerous studies have demonstrated the significant involvement of ILCs in both the onset and progression of this disease ( 35 , 36 ). The interaction between the nervous system and immune cells, such as ILCs, is complex and not fully understood ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of ILCs has been demonstrated in the pathogenesis of multiple sclerosis (MS), mostly by using experimental autoimmune encephalomyelitis (EAE), a model of MS ( Sadeghi Hassanabadi et al, 2022 ). EAE is induced in mice by active immunization with myelin antigens mixed with adjuvant ( Miller et al, 2010 ).…”
Section: Ilcs In Autoimmune Neuroinflammation Neurodegenerative Disea...mentioning
confidence: 99%